A facile synthesis of mesoporous PdZnO nanocomposites as efficient chemical sensor. (July 2016) - Ismail, Adel A.; Harraz, Farid A.; Faisal, M.; El-Toni, Ahmed Mohamed; Al-Hajry, A.; Al-Assiri, M.S.
Abstract: Mesoporous ZnO was synthesized through the sol-gel method in the presence of triblock co-polymer Pluronic (F-127) template as the structure directing agent. Palladium nanoparticles were photochemically reduced and deposited onto mesoporous ZnO to obtain 1 wt.% Pd/ZnO nanocomposite. Structural and morphological analysis revealed high homogeneity and monodispersity of Pd nanoclusters with small particle sizes ∼ 2–5 nm onto mesoporous ZnO. The electrochemical detection of ethanol in aqueous solutions was conducted at the newly developed Pd/ZnO modified glassy carbon electrode (GCE) by the current-potential ( IV ) and cyclic voltammetry ( CV ) techniques and compared with bare GCE or pure ZnO. The presence of Pd dopant greatly enhances the sensitivity of ZnO, and the obtained mesoporous Pd/ZnO sensor has an excellent performance for precision detection of ethanol in aqueous solution with low concentration. The sensitivity was found to be 33.08 μAcm −2 mM −1 at lower concentration zone (0.05–0.8 mM) and 2.13 μAcm −2 mM −1 at higher concentration zone (0.8–12 mM), with a limit of detection (LOD) 19.2 μM. The kinetics study of ethanol oxidation revealed a characteristic feature for a mixed surface and diffusion-controlled process. These excellent sensing characteristics make the mesoporous Pd/ZnO nanocomposite a good candidate for the production of high-performance electrochemical sensors at low ethanol concentration in aqueous solution. Graphical abstract: Highlights: Mesoporous Pd/ZnO was synthesized via sol-gel with small particle sizes ∼ 2–5 nm. The electrochemical detection of ethanol in aqueous solutions was conducted. The sensitivity was found to be 33.08 μAcm −2 mM −1 with a limit of detection 19.2 μM. The kinetics study revealed a mixed surface and diffusion-controlled processes.